Strategi Integrasi Kurikukum Studi Islam dan Bahasa Arab dalam Kemahiran Berbahasa dan Literasi Keberagamaan - Achmad Muharam Basyari (AL-IBANAH, 2025)
This study aims to analyze the strategy of integrating Islamic studies and Arabic language curricula in strengthening Arabic language proficiency and religious literacy at Ma’had Al Imarat Bandung. The research employed a qualitative method with a case study approach. Data were collected through direct classroom observations, in-depth interviews with administrators and educators, and curriculum document analysis. The findings reveal that the integration of Islamic studies and Arabic language curricula is implemented through a thematic approach, where Arabic language materials are contextualized within Islamic teachings. This strategy creates significant synergy in enhancing students’ Arabic language skills while simultaneously deepening their understanding of Islamic values comprehensively. This study contributes to the field of Islamic education by offering an effective and applicable model of curriculum integration. The implications suggest that strengthening language proficiency and religious literacy through integrated curricula can serve as a reference for curriculum development in other Islamic educational institutions, supporting the realization of holistic Islamic education goals.